KELIMPAHAN GULMA PEMANJAT PADA TANAMAN CEMARA UDANG DI SEKITAR EKOSISTEM AGRO, PANTAI SAMAS, BANTUL (study kasus di Kawasan Lahan Pasir Pantai Samas Bantul) - , ANAN TRI KUSUMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Casuarina equisetifolia is a plant that is now widely grown in the Samas Beach. Selection of this type because Casuarina equisetifolia can adapt to environment conditions beach. In the subsequent development of the samas coast at this time, ecosystem plantation in the back of Casuarina equisetifolia have been successfully be used as agro ecosystem area. But the problems arises that is the weeds climber that grows on Casuarina equisetifolia around the area of ecosystem agro. This research aims to identify the types of weeds climber and evaluate the abundance of the Casuarina equisetifolia which was near the area of ecosystem agro. The research was conducted in May and July 2013 in a plantation of Casuarina equisetifolia around of Samas beach, bantul, that is in Goa Cemara, Tambak Udang, and Mercusuar. Data collection was done by making plots by 4 plots at each location in the elderly and young (each age 2 plots) with the size of 400 m2. Making the plot is based on the lighting conditions of each tree that is open and shaded. Tren analysis is used to determine the distribution of weeds climber, weeds climber intensity, and its ability to adapt to do with shaded and open light conditions. Based on research, the type of weed climber known, that is Passiflora foetida. Wide Distribution (WD) and Intensity of Weeds Climber (IWC) based on the location of the study showed varied results, in old age the largest of locations is Mercusuar (WD=60 %, IWC=27,65%), second is Tambak Udang, that is (WD=25 %, IWC=12,5 %), and the smallest is Goa Cemara (WD= 0%, IWC= 0%). In young age the largest of locations is Tambak Udang (WD=56,25 %, IWC=29,16%), second is Goa Cemara (WD= 17,64%, IWC=7,38%), and the smallest is Mercusuar (WD= 0%, IWC=0%).